2014
DOI: 10.1161/circinterventions.113.000797
|View full text |Cite
|
Sign up to set email alerts
|

Incidences, Predictors, and Clinical Outcomes of Acute and Late Stent Malapposition Detected by Optical Coherence Tomography After Drug-Eluting Stent Implantation

Abstract: 5However, optical coherence tomography (OCT) with a higher resolution (12-18 μm) may detect stent malapposition with greater accuracy. There are limited data on detection of acute and late stent malapposition by OCT in small sample sizes. Therefore, we investigated the incidences, predictors, and clinical outcomes of acute and late stent malapposition detected by OCT in a large number of patients who received DESs. Editorial see p 6 Methods Study PopulationPatients who received implantation of DESs for de novo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
82
3
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 27 publications
(38 reference statements)
9
82
3
4
Order By: Relevance
“…In intravascular ultrasound study investigating the long-term prognosis of late stent malapposition that was detected at 6 months after DES implantation, the stent malapposition was not associated with any major adverse cardiac events during a subsequent 10-month follow-up (4). A similar finding was observed in an OCT study, in which adverse cardiac events did not occur in patients with late stent malapposition during follow-up of mean 28 months after DES implantation (5). Contrary to these studies, crosssectional OCT studies showed that the malapposition was a leading cause of early, late, or very late ST (3,6).…”
Section: Stent Malapposition and Under-expansionsupporting
confidence: 72%
See 1 more Smart Citation
“…In intravascular ultrasound study investigating the long-term prognosis of late stent malapposition that was detected at 6 months after DES implantation, the stent malapposition was not associated with any major adverse cardiac events during a subsequent 10-month follow-up (4). A similar finding was observed in an OCT study, in which adverse cardiac events did not occur in patients with late stent malapposition during follow-up of mean 28 months after DES implantation (5). Contrary to these studies, crosssectional OCT studies showed that the malapposition was a leading cause of early, late, or very late ST (3,6).…”
Section: Stent Malapposition and Under-expansionsupporting
confidence: 72%
“…Contrary to these studies, crosssectional OCT studies showed that the malapposition was a leading cause of early, late, or very late ST (3,6). These discrepancies were partly explained by the finding that stent malapposition could be spontaneously resolved over time (5,7). As a determinant for the resolution of stent malapposition, the distance between malapposed strut and vessel wall was proposed: the greater the distance, the more persistent the malapposition (8).…”
Section: Stent Malapposition and Under-expansionmentioning
confidence: 95%
“…Studies using optical coherence tomography (OCT) have reported a frequency of ASM that has ranged from 39.1% to 83.7%,19, 20, 21, 22 suggesting that it is ubiquitous after implantation if more sensitive methods are used to assess its frequency. Any finding seen in the majority of stents is of limited value in predicting adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Severe diameter stenosis and subsequent differences between the luminal diameter of the most stenotic segment and that of the reference vessel also increase the frequency of ASM 19. Heavily calcified lesions are prone to ASM, despite high‐pressure balloon dilation or rotational atherectomy 22, 23.…”
Section: Discussionmentioning
confidence: 99%
“…3B) may be related to persistent malapposition, 75) or delayed neointimal coverage, 78) but small incomplete stent apposition is not related to clinical events. [73][74][75][76]79) Tissue protrusion (Fig. 3C) may be related to neointimal hyperplasia, 80) but does not affect the occurrence of clinical events either.…”
Section: Evaluation Of Non-culprit Plaque Characteristicsmentioning
confidence: 98%